2014
DOI: 10.1210/jc.2014-2155
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Changes During the Pre-Receptive to Receptive Transition in Human Endometrium Detected by RNA-Seq

Abstract: This study provides the first RNA-Seq-based transcriptome comparison of pre-receptive and receptive human endometria. Many novel candidate genes, which have not been previously studied in human endometrium, may have functional significance during implantation and serve as molecular markers for endometrial receptivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 40 publications
5
71
0
1
Order By: Relevance
“…In order to overcome these limitations, we directly analysed lists of differentially expressed genes from nine published studies involving a total of 164 endometrial biopsy samples from healthy women. Using a method that has been specifically designed for comparison of gene lists and identification of commonly overlapping genes in various studies, including recently published transcriptome studies in different ethnic groups 30 , 37 , 38 , we hope to provide an up-to-date meta-signature of endometrial receptivity biomarkers. Nevertheless, we have to bear in mind that with our approach, analysing the significantly differentially expressed gene lists, we could have missed the potential biomarker genes that were below statistical significance in individual studies but could become relevant in a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome these limitations, we directly analysed lists of differentially expressed genes from nine published studies involving a total of 164 endometrial biopsy samples from healthy women. Using a method that has been specifically designed for comparison of gene lists and identification of commonly overlapping genes in various studies, including recently published transcriptome studies in different ethnic groups 30 , 37 , 38 , we hope to provide an up-to-date meta-signature of endometrial receptivity biomarkers. Nevertheless, we have to bear in mind that with our approach, analysing the significantly differentially expressed gene lists, we could have missed the potential biomarker genes that were below statistical significance in individual studies but could become relevant in a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome studies have demonstrated a myriad of changes in endometrial gene expression during the transition from pre-receptive to receptive phase 2, 3 , and a specific transcriptome signature has been detected that is now used to determine the individual WOI and aid in selecting the best day for embryo transfer in women undergoing in vitro fertilization 4 . Although the endometrial function is believed to be under epigenetic control 5 , less is known about how endometrial DNA methylation pattern changes throughout the menstrual cycle, what impact it has on gene expression, and whether aberrations in methylation pattern could lead to altered endometrial function.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported modifications in gene expression profiles associated with transition of the human endometrium from a pre‐receptive to a receptive stage (Cuevas et al, ; Díaz‐Gimeno et al, ; Hu et al, ; Sigurgeirsson et al, ). However, only two genes were common to six of the seven largest studies, secreted phosphoprotein 1 (SPP1; previously known as osteopontin) (Wang & Yu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analyses of distinct physiological stages were crucial for understanding the gene regulatory network, including the endometrium development in mammals (Wang et al, ; Zhang et al, , ). Moreover, studies on the endometrial transcriptomics have been reported using RNA‐Seq in humans (Hu et al, ), pigs (Lin et al, ; Samborski, Graf, Krebs, Kessler, & Bauersachs, ; Samborski, Graf, Krebs, Kessler, Reichenbach, et al, ; Wang et al, ), cattles (Mamo, Mehta, Forde, Mcgettigan, & Lonergan, ; Palma‐Vera, Sharbati, & Einspanier, ), and goats (Zhang et al, , ).…”
Section: Introductionmentioning
confidence: 99%